2023
DOI: 10.1186/s12967-023-04013-w
|View full text |Cite
|
Sign up to set email alerts
|

CRS: a circadian rhythm score model for predicting prognosis and treatment response in cancer patients

Abstract: Background Circadian rhythm regulates complex physiological activities in organisms. A strong link between circadian dysfunction and cancer has been identified. However, the factors of dysregulation and functional significance of circadian rhythm genes in cancer have received little attention. Methods In 18 cancer types from The Cancer Genome Atlas (TCGA), the differential expression and genetic variation of 48 circadian rhythm genes (CRGs) were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…BC is a highly heterogeneous disease, with multiple genetic, environmental, and lifestyle factors involved in its pathogenesis, the precise mechanisms of which have not been completely defined [ 60 ]. Increasing evidence suggests that circadian rhythms regulate physiological processes like cell cycle, metabolism, and immune function, thereby influencing BC risk, progression, and prognosis [ [61] , [62] , [63] , [64] ]. Therefore, we investigated the risk, prognosis, and immunological microenvironment of BC from the perspective of CRGs.…”
Section: Discussionmentioning
confidence: 99%
“…BC is a highly heterogeneous disease, with multiple genetic, environmental, and lifestyle factors involved in its pathogenesis, the precise mechanisms of which have not been completely defined [ 60 ]. Increasing evidence suggests that circadian rhythms regulate physiological processes like cell cycle, metabolism, and immune function, thereby influencing BC risk, progression, and prognosis [ [61] , [62] , [63] , [64] ]. Therefore, we investigated the risk, prognosis, and immunological microenvironment of BC from the perspective of CRGs.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have previously explored the effects of circadian rhythm-associated genes on different tumors. Brooks et al [ 54 ] found that circadian rhythm-related lncRNA ADIRF-AS1 drove clear cell renal carcinoma progression through targeting PBAF; Zhang et al [ 55 ] constructed a model of circadian rhythm-associated lncRNAs that stably predicted the prognosis of hepatocellular carcinoma with a significant impact to the immune infiltration status of the tumor; Liu et al [ 56 ] constructed a circadian rhythm-associated gene risk model to predict survivals in patients with melanoma, non-small-cell lung cancer, and glioma, and could differentiate the immune cell infiltration status in these patients. This research is the first to construct a circadian rhythm-associated lncRNAs prognostic prediction model for the precise prediction of prognosis in osteosarcoma patients.…”
Section: Discussionmentioning
confidence: 99%